HISTÓRICO E PERSPECTIVAS DA UTILIZAÇÃO DE MACROINVERTEBRADOS NO MONITORAMENTO BIOLÓGICO DE ECOSSISTEMAS AQUÁTICOS NO BRASIL - Docile, Tatiana Nascimento; Figueiró, Ronaldo (Acta Scientiae et Technicae; v. 1 n. 1 (2013): I Simpósio de Biotecnologia e Biodiversidade, 2013)
Biomonitoring can be defi ned as the sistematic use of the biological response of organisms to evaluate the enviromental changes, generally antropogenical. The urbanization has translated in growing antropogenic impacts in ecosystems, which can be evaluated through the evaluaton of its respective biological communities. In the present article, a brief history of biomonitoring, both as a concept and as a tool applied to integrated management. The main indices are presented and discussed, aiming to establish the current picture of the use of this tool in Brazil and in the rest of the world.